A Survey on Usage of Rubber Dam during Composite Restorative Procedures by General and Specialist Dental Practitioners in Saudi Arabia - AlQarni, Mohammed Ali (Journal of Orofacial Research, 1970)
Aim: The purpose of this study was to quantify the usage of rubber dam (RD) among general and specialty dental practitioners during composite restorative procedures in Saudi Arabia. Materials and methods: A cross-sectional questionnaire-based study was conducted from March to April 2012 in association with Saudi Dental Society on 306 general dental practitioners (GP), dentists specialized in operative dentistry (OD) and other specialty dentists (OSD). The collected data were analyzed using Microsoft Excel 2010 program and descriptive statistics were obtained. Results: For isolation during composite restorative procedures in anterior teeth, 21.2% of GP, 57.1% of OD and 29.6% of OSD use RD; 77.5% of GP, 42.9% of OD and 68.5% of OSD use cotton rolls and 1.3% of GP and 1.9% of OSD use methods other than RD or cotton rolls. For isolation during composite restorative procedures in posterior teeth, 28.8% of GP, 62.5% of OD and 40.7% of OSD use RD; 68.7% of GP, 35.7% of OD and 57.4% of OSD use cotton rolls and 2.5% of GP, 1.8% of OD and 1.9% of OSD use other methods. Conclusion: There is under-usage of RD during placement of composite restorations by dentists in the study population. Majority of the dentists practicing RD are those who have specialized in OD.